2020
DOI: 10.21203/rs.3.rs-15806/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Internet addiction mediates the association between cyber victimization and psychological and physical symptoms:moderation by physical exercise

Abstract: Background: The potential mechanisms underlying cyber victimization and the resulting psychological and physical symptoms remain unclear. Thus, the present study investigated whether Internet addiction mediates the association between peer victimization (e.g., cyberbullying) and psychological and physical symptoms. Furthermore, it was assessed whether physical exercise moderates the hypothetical mediation.Methods: 1,854 students from 11 middle and high schools in Shenzhen, Guangdong Province, China, were sampl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 22 publications
0
5
0
2
Order By: Relevance
“…Compared with traditional victimization, cybervictimization involves more extreme violations of personal privacy, coupled with the perpetrators ability to remain anonymous as well as to harass others without being constrained by time and place ( Kowalski et al, 2018 ), which may lead to more psychological and behavioral problems for the victim ( Sourander et al, 2010 ). Some empirical evidence has supported the view that cybervictimization has a high correlation with adolescents’ IA ( Gamez-Guadix et al, 2013 ; Chang et al, 2015 ; Lin et al, 2020 ). For example, using a longitudinal study, Gamez-Guadix et al (2013) found that cybervictimization significantly predicted problematic internet use 6 months later among adolescents.…”
Section: Introductionmentioning
confidence: 96%
“…Compared with traditional victimization, cybervictimization involves more extreme violations of personal privacy, coupled with the perpetrators ability to remain anonymous as well as to harass others without being constrained by time and place ( Kowalski et al, 2018 ), which may lead to more psychological and behavioral problems for the victim ( Sourander et al, 2010 ). Some empirical evidence has supported the view that cybervictimization has a high correlation with adolescents’ IA ( Gamez-Guadix et al, 2013 ; Chang et al, 2015 ; Lin et al, 2020 ). For example, using a longitudinal study, Gamez-Guadix et al (2013) found that cybervictimization significantly predicted problematic internet use 6 months later among adolescents.…”
Section: Introductionmentioning
confidence: 96%
“…Internet addiction has been reported to be almost 47.7% in a study by Lin et al (2020). It is significantly related to social isolation, depressive disorder and other adverse health consequences which worsen the condition of victims of cyberbullying.…”
Section: Internet Usage and Addictionmentioning
confidence: 99%
“…Internet addiction has a bidirectional association with cyberbullying and risky behavior such as chatting with strangers, posting personal information and pictures, etc. (Lin et al, 2020). Internet addiction is the uncontrollable, excessive and compulsive use of the internet.…”
Section: Internet Usage and Addictionmentioning
confidence: 99%
“…Örneğin internet bağımlılığının aracı etkisi ile siber mağduriyet ve fiziksel-psikolojik semptomların ilişkisinin incelendiği bir çalışmada aracılık etkisinin anlamlı düzeyde olduğu belirlenmiştir. Ayrıca aynı çalışmada egzersizin sağlık sonuçları üzerinde olumlu yönde dönüştürücü etkisi olduğu da bildirilmiştir (31). Yatay ve dikey bireyciliğin internet bağımlılığı üzerinden siber zorbalığa olan etkisinin incelendiği bir diğer çalışmada ise dikey bireyciliğin internet bağımlılığı üzerinden siber zorbalık üzerinde kısmi aracı etkiye sahip olduğu gösterilmiştir (32).…”
Section: Introductionunclassified
“…Bu bağlamda ergenlerin siber mağduriyet ve zorbalığa götüren yolda internet kullanımına olan bağımlılık aracılık etmektedir. İnternet bağımlılığı diğer çalışlardaki gibi aracılık etkisi yoluyla sonuçlar üzerinde etki göstermektedir(31,32).Aile iletişimi ve akran ilişkilerinin siber mağduriyet yaşamada ve siber zorba olmada etkili olduğu görülmektedir. Aynı zamanda internet bağımlılığını da etkilemektedir.…”
unclassified